Antioxidant Activity and Organoleptic Quality of Purple Chrysanthemum (Chrysanthemum morifolium) Kombucha on the Variation of Sugar Types and Fermentation Duration - Ikromi, Aflah; Suryani, Titik (Green Engineering Society, 2025)
Kombucha is one of the probiotic beverages resulting from the fermentation of tea with a consortium of bacteria and yeast (Symbiotic Culture of Bacteria and Yeast / SCOBY) as the starter culture requiring sugar as source of nutrients and carbon. One innovation of kombucha raw materials is purple chrysanthemum flowers containing active compounds such as carotenoids, flavonoids, and anthocyanins. The aim of this study was to determine the antioxidant activity and organoleptic quality of kombucha from purple chrysanthemum flower on the variation of sugar types and fermentation duration. This research method used an experimental method with 2 factors, Completely Randomized Design (CRD). Factor I: variation of sugar types (G): palm sugar and Javanese sugar. Factor II: fermentation duration (F): 5 days and 7 days, green tea kombucha as control. Data analysis of antioxidant activity and vitamin C used quantitative descriptive methods, while organoleptic quality used qualitative methods. It was concluded that the highest antioxidant activity and the best organoleptic quality of purple chrysanthemum kombucha was 76.37% with brown color, quite fragrant of kombucha, quit sour taste, and preferred by the panelists in the G1F2 treatment (200g of palm sugar with fermentation duration of 7 days).